Challenges and Opportunities in Early Childhood Religious and Moral Education: A Perspective from the Evaluation of Logical Models - Istiyani, Dwi; Wibowo, A.M; Taruna, Mulyani Mudis; Rahmawati, Titik; Atmanto, Nugroho Eko (Nazhruna: Jurnal Pendidikan Islam, 2024)
This study is an evaluation that aims to analyze the development of religious and moral values aspects of early childhood. The method used is a qualitative method, where data are collected through in-depth discussions with a logical model evaluation analysis in early childhood religious and moral values (NAM) development programs. The results of the study found three important things, namely first, so far value-based learning for early childhood is done through understanding religious symbols, daily routine worship practices, and daily prayers, while moral strengthening is done through fairy tales containing good values. Understanding and strengthening religious moral values in early childhood is implemented variably according to the needs of each school. This study also identified some weaknesses in the cultivation of religious and moral values in early childhood, namely routine activities that can obscure children's understanding and children's lack of enthusiasm due to mistakes in approaches that are not adapted to psychological development. Variations in teaching methods that are not appropriate for children's psychology can cause a distorted understanding of religious and moral values to become shallow. A holistic and diverse approach that takes into account the needs and characteristics of each child is needed to ensure that the cultivation of religious and moral values is effective and sustainable.